HUBUNGAN PENDAPATAN PERKAPITA, PENGETAHUAN GIZI IBU DAN AKTIVITAS FISIK DENGAN OBESITAS ANAK KELAS 4 DAN 5 DI SD HJ. ISRIATI BAITURRAHMAN KOTA SEMARANG - Setiawan Hadi M; Enik Sulistyowati; Mifbakhudin - (Jurnal Kesehatan Masyarakat Indonesia, 2005)
Background: the average rate of obesity among children in Indonesia is 9.2%. In Semarang, there was 9, 69% case of over nutrition among children betvveen the year of 1999 to 2000. This could trigger many genercttive diseases such as hypertension, coronary heart disease, cancer and diabetic mellitus. There are many factors related to obesity including the family financial income, mother's knowledge and understanding about nutrition, and the physical activity of the children.Method; this explanatory study applies the cross-sectional survey method. The population is all 4'h awl 5'h gracle students of SD Hj Isriati Baiturrahman with total samples of 44 students. The variables are obesity, income per capita, mother's knowledge about nutrition, physical activity. The statistical test implemented in this study is the Pearson Product Moment, and the Rank Spearman correlation method. Result: most students have the Z score > 2, The cverage rate for student's age:9,26*0,S4,averagebodyweight:56,31Kg+l,35,bodyheightl43,63cm*6,73,incomepercapitaRp.888.68l,-*279.507.average mother's knowledge: 96,44 * 4,13. Average energy released: 53 kalori / day + 225,01. There is a signiJicant con'elation between family income with obesity with p < 0,05 and r : 0,653, mother's knowledge about nutrition with obesity with the value of p < 0,05 and r : -0,483, there is no significant correlation between physical activity with obesity with the value of p = 0,164. Conclusion: there is a relationship betvveen income per capita and mother's knowleclge aboqt nutrition with obesity. Yet, there is no relation between physical activity with obesity among 4'h and 5'h grade students of SD Hj. Isriati Baiturrahman, Semarang.Keywords: obesity, income per capita, mother's knowledge on nutrition with obesity, and children's physical activity